N-glycosylation of carnosinase influences protein secretion and enzyme activity: implications for hyperglycemia - Riedl, Eva; Köppel, Hannes; Pfister, Frederick; Peters, Verena; Hauske, Sibylle J.; Sternik, Paula; Brinkkötter, Paul-Thomas; Zentgraf, Hanswalter; Navis, Gerjan; Henning, Robert H.; Van Den Born, Jacob; Bakker, Stephan J.L.; et al. (Diabetes, 2010)
The (CTG)n polymorphism in the serum carnosinase (CN-1) gene affects CN-1 secretion. Since CN-1 is heavily glycosylated and glycosylation might influence protein secretion as well, we tested the role of N-glycosylation for CN-1 secretion and enzyme activity. We also tested whether CN-1 secretion is changed under hyperglycemic conditions.N-glycosylation of CN-1 was either inhibited by tunicamycin in pCSII-CN-1-transfected Cos-7 cells or by stepwise deletion of its three putative N-glycosylation sites. CN-1 protein expression, N-glycosylation, and enzyme activity were assessed in cell extracts and supernatants. The influence of hyperglycemia on CN-1 enzyme activity in human serum was tested in homozygous (CTG)5 diabetic patients and healthy control subjects.Tunicamycin completely inhibited CN-1 secretion. Deletion of all N-glycosylation sites was required to reduce CN-1 secretion efficiency. Enzyme activity was already diminished when two sites were deleted. In pCSII-CN-1-transfected Cos-7 cells cultured in medium containing 25 mmol/l d-glucose, the immature 61 kilodaltons (kDa) CN-1 immune reactive band was not detected. This was paralleled by an increased GlcNAc expression in cell lysates and CN-1 expression in the supernatants. Homozygous (CTG)5 diabetic patients had significantly higher serum CN-1 activity compared with genotype-matched, healthy control subjects.We conclude that apart from the (CTG)n polymorphism in the signal peptide of CN-1, N-glycosylation is essential for appropriate secretion and enzyme activity. Since hyperglycemia enhances CN-1 secretion and enzyme activity, our data suggest that poor blood glucose control in diabetic patients might result in an increased CN-1 secretion even in the presence of the (CTG)5 allele.
Gesehen am 15.05.2023